упростите выражение:( а² + a-b - 2 ) / ( a+b - b-a - 4a² ) = b³-ab² b² b b-a b+a...

0 голосов
66 просмотров

упростите выражение:( а² + a-b - 2 ) / ( a+b - b-a - 4a² ) =

b³-ab² b² b b-a b+a a²-b²


Алгебра (27 баллов) | 66 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

(\frac{a^{2}}{b^{3}-ab^{2}} + \frac{a-b}{b^{2}} - \frac{2}{b} ) / (\frac{a+b}{b-a}-\frac{b-a}{b+a}-\frac{4a^{2}}{a^{2}-b^{2}}) =

 

1) (\frac{a^{2}}{b^{3}-ab^{2}} + \frac{a-b}{b^{2}} - \frac{2}{b} = \frac{a^{2}-(a-b)^{2}-2b(b-a) }{b^{2}(b-a)} = \frac{a^{2}-a^{2}+2ab-b^{2}-2b^{2}+2ab }{b^{2}(b-a)} =\frac{4ab-3b^{2}}{b^{2}(b-a)} = \frac{b(4a-3b)}{b^{2}(b-a)} = \frac{4a-3b}{b(b-a)}

 

2)\frac{a+b}{b-a}-\frac{b-a}{b+a}-\frac{4a^{2}}{a^{2}-b^{2}} = -\frac{a+b}{a-b}-\frac{b-a}{a+b}-\frac{4a^{2}}{a^{2}-b^{2}} = \frac{(a+b)^{2}+(a-b)^{2}-4a^{2}}{a^{2}-b^{2}} =\frac{a^{2}+2ab+b^{2}+a^{2}-2ab+b^{2}-4a^{2}}{a^{2}-b^{2}} = \frac{2b^{2}-2a^{2}}{a^{2}-b^{2}} = \frac{-2(a^{2}-b^{2})}{a^{2}-b^{2}} = -2

 

3)\frac{4a-3b}{b(b-a)} / (-2) = \frac{4a-3b}{b(b-a)} * (-\frac{1}{2}) = \frac{3b-4a}{2b(b-a)}

 

Ответ. \frac{3b-4a}{2b(b-a)}

(90.4k баллов)